Bright – Experience - F. Orosz, Sára (Studia Mundi – Economica, 2015)
Expressions of the culture and bright in the art history of the worldThe role of brightness has beenvery important from the beginning of the cultural history of mankind. Different ages have had different interpretationsof the image they created about it. Paintings, sculptures and many other art pieces have visible expressions ofit. What is the point of view behind the unity of the idea and the expression of light? The essay provides a greater insight into the diverse ideas of different artists from different parts of the world.
Keywords: brightness; visual art; ancient and contemporary art; fine and applied art; art history